645 Evaluation of the bioclimate of the Piatra Neamț tourist resort (Balneo and PRM Research Journal, 2024)
: The study responds to real needs of knowing the bioclimate of some tourist resorts in order to develop different types of tourism, in which the bioclimate plays a significant role. In Romania, a similar study was carried out for the resort towns of Vatra Dornei and Tg. Ocna. Methods: The research is based on time series of weather elements from 1961-2021. These series were used for the calculation of the bioclimatic index of the physiological equivalent temperature (PET) which allows the analysis of the temporal peculiarities of the bioclimate. In order to highlight in a new perspective the relationship between biocli-mate and tourism in the Piatra Neamț resort, we created climate-tourism schemes (CTIS). Results: PET values ranged between a maximum of 35.7°C (severe thermal stress due to heating) and a minimum of - 29.3°C (extreme thermal stress due to cooling). The mean PET value was 8.8°C (indicating moderate cold stress). The period of the year with biocli-matic comfort, for hiking, visiting, outdoor sports, climatotherapy, balneotherapy corresponds to the interval April (3rd decade) - October (1st decade). Conclusions: Tourists who want to plan their vacation in Piatra Neamț will benefit from non-restrictive bioclimatic conditions from the end of April to the beginning of October. During the cold season, with a layer of snow, winter sports can be practiced. Keywords: bioclimate, bioclimatic comfort, bioclimatic stress, PET index, CTIS